Elderly men with prostate cancer: Meanings attributed to the disease and sexuality (Research, Society and Development, 2022)
Prostate cancer is the fifth most common in the world and the second among men, with more than half of the affected population being elderly. Both younger men affected by prostate cancer and the elderly suffer prejudice and taboos in relation to sexuality. Therefore, the objective study analyzes, in the speeches of elderly men with prostate cancer, the meanings attributed to the disease and sexuality. This is a basic, descriptive, exploratory, explanatory study with a qualitative approach that was carried out with 20 men, from September to October 2022, carried out in a medium-sized private hospital in the interior of Bahia and in an institution that supports people with cancer, with elderly men aged 60 or over, with prostate cancer. The raised speeches were transcribed literally and analyzed qualitatively, through the content analysis method defined by Laurence Bardin. From the analysis, categories were structured, namely: signs and symptoms, inefficiency of communication/information about the disease and sexuality, diagnosis and its taboos, changes related to usual and sexual activity and fears and insecurities in sexual relations after the diagnosis of CP. It is concluded that the experiences described by the elderly in the interviews demonstrate that the cancer process can bring social deprivation in everyday life and the possibility of taking away from their duties, both mandatory and leisure, and that the treatment and its side effects affected the sexual life of the participants.